1969
DOI: 10.1111/j.1469-8986.1969.tb02900.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalization of GSR Habituation to Mild Intramodal Stimuli

Abstract: Subjects habituated to a mild stimulus failed to have GSRs upon the intrusion of a "novel" mild intramodal stimulus. However, an intruding intermodal stimulus of approximately the same intensity caused large GSRs. These results support an explanation based on expectancy or the "neuronal model" of Sokolov, provided suitable allowance is made for changes in specificity of the model as a result of variations in the experimental situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…A presentation of an unexpected number (e.g., 21, 22, 23,..., 600) did not produce an enhanced electrodermal response. Houck and Mefferd (1969) obtained a significant increase in electrodermal responsivity to a stimulus change only across but not within stimulus modality. Furthermore, Bernstein (1969) indicated that even in experiments in which a stimulus change did produce an OR, there were marked individual differences, and in many subjects the effect of stimulus change was not observed.…”
mentioning
confidence: 86%
“…A presentation of an unexpected number (e.g., 21, 22, 23,..., 600) did not produce an enhanced electrodermal response. Houck and Mefferd (1969) obtained a significant increase in electrodermal responsivity to a stimulus change only across but not within stimulus modality. Furthermore, Bernstein (1969) indicated that even in experiments in which a stimulus change did produce an OR, there were marked individual differences, and in many subjects the effect of stimulus change was not observed.…”
mentioning
confidence: 86%
“…Changes in stimuli are ultimately more important than the actual content of stimuli in determining the characteristics of the OR and habituation. When a series of stimuli is presented in one sensory modality (e.g., visual) and is then switched to another modality (e.g., sound), there is a large recovery of the OR (Furedy, 1968;Houck & Mefferd, 1969). Changes in tone, stimulus intensity, stimulus duration, stimulus omission, and word meaning have been shown to cause the reemergence of the OR (see Siddle et al, 1983, for a review).…”
Section: Stimulus Uncertainty and Changementioning
confidence: 99%
“…Indeed, with the accumulation of research data, more instances were reported in which a change in stimulation failed to evoke an OR~e.g., Bernstein, 1969;Furedy, 1968;Houck & Mefferd, 1969;Zimny, Pawlick, & Saur, 1969!. It is difficult to determine whether these instances should be interpreted as refutations of Sokolov's theory, because it is not clear whether a given change in stimulation was insufficient to create an orientation, or whether the fact that the change did not produce a response is an indication that the whole comparator approach is invalid.…”
mentioning
confidence: 99%